Attractive function of female images in fiction (by Belarusian prose of 1920–30s) - Tscharnavokaya, Аleksandra M. (Journal of the Belarusian State University. Philology, 2019)
The article presents the results of a comparative analysis of the images of «femme fatale», «woman-temptress» and «girl-victim» in the works of Jadvihin Sh., Zmitrok Bjadulja, Michas Zarecki, Michas Lynkou. The study found, that female characters of these types perform an attractive function – they are a «lure» for the the main character and for the reader. The purpose of this article is to determine the characteristics of attractive female images using methods and approaches of gender studies. It’s concluded, that attractive female images represent the stereotypes of femininity; they are schematic and one-dimensional. The character is represented as a sexual object; intriguing circumstances of woman’s personal life are frequently accented. Dynamic deconcentrated description compensates for the static nature of the image. It’s noted, that in many works of these period a love story is introduced to interest the reader in described social and political processes. The results of the research clarify the typology of female images based on their functions and help to characterize one of the most common approaches to the construction of female characters.
Keywords: character; typology; functionality; psychologism; amplua; stereotypes of femininity; Jadvihin Sh.; Zmitrok Bjadulja; Michas Zarecki; Michas Lynkou